2023
DOI: 10.3390/nu15092140
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and Central Nervous System Disorders

Abstract: Zinc (Zn2+) is the second most abundant necessary trace element in the human body, exerting a critical role in many physiological processes such as cellular proliferation, transcription, apoptosis, growth, immunity, and wound healing. It is an essential catalyst ion for many enzymes and transcription factors. The maintenance of Zn2+ homeostasis is essential for the central nervous system, in which Zn2+ is abundantly distributed and accumulates in presynaptic vesicles. Synaptic Zn2+ is necessary for neural tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 262 publications
1
7
0
Order By: Relevance
“…Our findings of cognitive improvement are corroborated by previous studies that have shown neuroprotective properties, anti-inflammatory, and antioxidant effects of Zn [35,36]. The imbalance in zinc ion (Zn 2+ ) levels appears to play a crucial role in the etiology and progression of neurodegenerative diseases [5], such as Alzheimer's disease (AD), Parkinson's, attention deficit hyperactivity disorder (ADHD) [37][38][39][40], as well as psychiatric disorders [41]. Zinc deficiency is associated with AD, while Zn supplementation has been linked to a reduced prevalence of AD and slowed disease progression [37].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings of cognitive improvement are corroborated by previous studies that have shown neuroprotective properties, anti-inflammatory, and antioxidant effects of Zn [35,36]. The imbalance in zinc ion (Zn 2+ ) levels appears to play a crucial role in the etiology and progression of neurodegenerative diseases [5], such as Alzheimer's disease (AD), Parkinson's, attention deficit hyperactivity disorder (ADHD) [37][38][39][40], as well as psychiatric disorders [41]. Zinc deficiency is associated with AD, while Zn supplementation has been linked to a reduced prevalence of AD and slowed disease progression [37].…”
Section: Discussionsupporting
confidence: 89%
“…Zinc is regulated by complex mechanisms of absorption, transport, and excretion, which aim to keep zinc levels in balance. Deregulations in this homeostasis can lead to deficiencies or excesses of zinc concentrations, both harmful to the central nervous system (CNS) and health [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…A consensus is coalescing around the idea that altered homeostatic levels of Zn 2+ play a significant role in many neurological disorders. These disorders (reviewed by Wang et al 84 ) include neurodegenerative conditions such as Alzheimer's disease (AD), Parkinson's disease (PD), and multiple sclerosis (MS); psychiatric disorders such as depression and schizophrenia; epilepsy; and traumatic brain injury. In the case of neurodegenerative disorders, especially PD, it is important to understand how DA regulation is altered.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Disruptions to Zn 2+ homeostasis might be associated with several disorders affecting the central nervous system, like Alzheimer's disease, Parkinson's disease, and depression [35]. Some Zn 2+ -containing transcription factors such as NF-κB and the tumour protein P53 (p53) participate in amyloid precursor protein (APP) synthesis.…”
Section: Zinc (Zn)mentioning
confidence: 99%